chức tỏ rằng:
(3+3^2+3^3+3^4+3^5+3^6+3^7+3^8+3^9)chia hết cho 13
dễ ha
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(S=\left(1+3\right)+...+3^8\left(1+3\right)\)
\(=4\left(1+...+3^8\right)⋮4\)
\(S=1+3+3^2+...+3^9\)
Ta có: \(S=\left(1+3\right)+\left(3^2+3^3\right)+...+\left(3^8+3^9\right)\)
\(S=4+3^2.\left(1+3\right)+...+3^8.\left(1+3\right)\)
\(S=4+3^2.4+...+3^8.4\)
\(S=4.\left(1+3^2+...+3^8\right)\)
Vì \(4⋮4\) nên \(4.\left(1+3^2+...+3^8\right)⋮4\)
Vậy \(S⋮4\).
\(#NqHahh\)
\(6+6^2+\cdot\cdot\cdot+6^{10}\)
\(=6\cdot\left(1+6\right)+6^3\cdot\left(1+6\right)+\cdot\cdot\cdot+6^9\cdot\left(1+6\right)\)
\(=6\cdot7+6^3\cdot7+\cdot\cdot\cdot+6^9\cdot7\)
\(=7\cdot\left(6+6^3+\cdot\cdot\cdot+6^9\right)⋮7\)
\(\Rightarrow6+6^2+\cdot\cdot\cdot\cdot+6^{10}⋮7\)
Ta có: A= 3+3\(^2\)+3\(^3\)+3\(^4\)+3\(^5\)+3\(^6\)+3\(^7\)+3\(^8\)+3\(^9\)+3\(^{10}\)
\(\Rightarrow\)A= (3+3\(^2\)) +(3\(^3\)+3\(^4\))+(3\(^5\)+3\(^6\)) +(3\(^7\)+3\(^8\))+(3\(^9\)+3\(^{10}\))
\(\Rightarrow\) A= 12 + 3\(^2\)(3\(^1\)+3\(^2\))+3\(^4\)(3\(^1\)+3\(^2\)) +3\(^6\)(3\(^1\)+3\(^2\)) + 3\(^8\)(3\(^1\)+3\(^2\))
\(\Rightarrow\) A= 12 + 3\(^2\). 12+3\(^4\) . 12+3\(^6\) .12+ 3\(^8\) .12
\(\Rightarrow\)A= 12 . ( 3\(^2\)+3\(^4\) +3\(^6\)+ 3\(^8\))
Vì 12 \(⋮\)4 \(\Rightarrow\)12 . ( 3\(^2\)+3\(^4\) +3\(^6\)+ 3\(^8\)) \(⋮\)4 hay A \(⋮\)4
\(3+3^2+3^3+3^4+.....+3^9.\)
\(=\left(3+3^2+3^3\right)+\left(3^4+3^5+3^6\right)+\left(3^7+3^8+3^9\right)\)
\(=3.\left(1+3+3^2\right)+3^4.\left(1+3+3^2\right).3^7.\left(1+3+3^2\right)\)
\(=3.13+3^4.13+3^7.13\)
\(=13.\left(3+3^4+3^7\right)\)
Vì \(13⋮13\Rightarrow13.\left(3+3^4+3^7\right)⋮13\)
Vậy \(3+3^2+3^3+3^4+3^5+3^6+3^7+3^8+3^9⋮13\)
3+3^2+3^3+3^4+3^5+3^6+3^7+3^8+3^9
= (3+3^2+3^3)+(3^4+3^5+3^6)+(3^7+3^8+3^9)
= 3.(1+3+3^2)+3^4.(1+3+3^2)+3^7.(1+3+3^2)
= 3.13+3^4.13+3^7.13
= 13. ( 3+3^4^3^7) chia hết cho 13